Community‐based, point‐of‐care hepatitis C testing: perspectives and preferences of people who inject drugs. Issue 7 (1st April 2019) - Latham, Ned H.; Pedrana, Alisa; Doyle, Joseph S.; Howell, Jessica; Williams, Bridget; Higgs, Peter; Thompson, Alexander J.; Hellard, Margaret E.
Summary: A barrier to hepatitis C treatment for people who inject drugs (PWID) is needing to attend multiple appointments for diagnosis. Point‐of‐care hepatitis C tests provide results within 20 to 105 minutes and can be offered opportunistically in nonclinical settings such as needle syringe programmes. In this nested qualitative study, we explored the acceptability of point‐of‐care testing for PWID. PWID attending participating needle syringe programmes were screened using the OraQuick HCV antibody mouth swab (result in 20 minutes); those with a reactive result then underwent venepuncture for a point‐of‐care RNA test: the Xpert HCV Viral Load (result in 105 minutes). Convenience sampling was used to select participants for a semi‐structured interview. A hybrid thematic analysis was performed, guided by Sekhon's "Theoretical Framework of Acceptability." Nineteen participants were interviewed. Three core themes emerged: "people and place, " "method of specimen collection, " and "rapidity of result return." It was highly acceptable to be offered testing at the needle syringeprogrammes by nurses and community health workers, who were described as competent and nonjudgemental. Most participants reported that even if a finger‐stick point‐of‐care RNA test were an option in the future, they would prefer venepuncture, as the sample could be used for pre‐treatment workup and bundled testing. Waiting 20 minutes to receive the antibody test result was acceptable, whereas the 105 minutes required for the RNA result was unacceptable. Offering point‐of‐care hepatitis C testing at needle syringe programmes is acceptable to PWID, however tests that avoid venepuncture are not necessarily the most attractive to PWID. Abstract : Three core themes emerged from our analysis of the acceptability of point‐of‐care hepatitis C antibody and RNA testing at needle syringe programs: "people and place, " "method of specimen collection, " and "rapidity of result return." Offering point‐of‐care hepatitis C testing in this setting is highly acceptable to people who inject drugs. Point‐of‐care tests that avoid venepuncture are not necessarily preferred as they cannot be used for pre‐treatment workup and bundled testing for other blood‐borne viruses.